2020
DOI: 10.3390/s20195535
|View full text |Cite
|
Sign up to set email alerts
|

Space-Borne GNSS-R Ionospheric Delay Error Elimination by Optimal Spatial Filtering

Abstract: Global Navigation Satellite System Reflectometry (GNSS-R) technology is a new and promising remote sensing technology, especially satellite-based GNSS-R remote sensing, which has broad application prospects. In this work, the ionospheric impacts on space-borne GNSS-R sea surface altimetry were investigated. An analysis of optimal values for spatial filtering to remove ionospheric delays in space-borne GNSS-R altimetry was conducted. Considering that there are few satellite-borne GNSS-R orbit observations to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Zhang Qiuyang analyzed the corresponding ionospheric delay measurement values in eight different regions of the world in the spaceborne GNSS-R experiment (Zhang et al, 2020a), and the results showed a meter-level accuracy. Among them, the ionospheric delay at a place close to this experimental site shows a fluctuation of about 6 m. In the experiment, Zhang Yun used the international reference ionospheric model to conduct ionospheric correction on the spaceborne GNSS-R altimetry experiment and the delay error was about 15 m (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang Qiuyang analyzed the corresponding ionospheric delay measurement values in eight different regions of the world in the spaceborne GNSS-R experiment (Zhang et al, 2020a), and the results showed a meter-level accuracy. Among them, the ionospheric delay at a place close to this experimental site shows a fluctuation of about 6 m. In the experiment, Zhang Yun used the international reference ionospheric model to conduct ionospheric correction on the spaceborne GNSS-R altimetry experiment and the delay error was about 15 m (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The geometric model of altimetry is shown in Figure 4, and the compensation of ionospheric delay and tropospheric delay also needs to be deeply studied. Zhang et al [123] investigated the effect of the ionosphere on spaceborne altimetry and analyzed the optimal value of spatial filtering to eliminate the ionospheric delay in altimetry. Cardellach et al [124] used the GA carrier phase of the GPS and Galileo signals from the CYGNSS data for altimetry, and the results showed that the measurement precision was 3 cm/4.1 cm (median/mean) at a sampling rate of 20 Hz.…”
Section: Spaceborne Sea Surface Altimetry and Land Topography 41 Sea ...mentioning
confidence: 99%